2017
DOI: 10.1002/pon.4328
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of depression and anxiety among women newly diagnosed with breast or genital organ cancer in Germany

Abstract: Women diagnosed with BC were at a higher risk of developing depression or anxiety than women with GOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 32 publications
(43 reference statements)
2
13
0
Order By: Relevance
“… 12 14 The therapeutic approach to breast cancer is based on a large body of evidence, 15 – 18 and there is increasing interest but still very limited data regarding attending psychiatric diseases in female patients with gynecologic, genital, and cervical cancer. 19 21 Patients suffering from different types of gynecologic cancer (genital/cervical cancer) may also have an increased risk of developing an attending psychiatric disease, but little is known about attending psychiatric disorders in patients with cancers other than breast cancer, such as gynecologic cancer.…”
Section: Introductionmentioning
confidence: 99%
“… 12 14 The therapeutic approach to breast cancer is based on a large body of evidence, 15 – 18 and there is increasing interest but still very limited data regarding attending psychiatric diseases in female patients with gynecologic, genital, and cervical cancer. 19 21 Patients suffering from different types of gynecologic cancer (genital/cervical cancer) may also have an increased risk of developing an attending psychiatric disease, but little is known about attending psychiatric disorders in patients with cancers other than breast cancer, such as gynecologic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In a study including 29366 patients with breast and gynecological cancers and investigating the incidence of depression/anxiety in patients, depression incidence was found to be 8.8% and 5.9% respectively in patients with breast and gynecological cancer and it was demonstrated that the risk of depression was 1,41 fold higher in patients with breast cancer than those with gynecological cancer. In the same study, it was stated that the risk of depression was 1.40 times higher in patients with metastasis than those with metastasis (24). In a retrospective study with 1101 patients investigating the relation between depression, disease stage and mortality in patients with prostate cancer, depression was found to be more common in patients with metastasis than those who are in early/local advanced stage.…”
Section: Discusssionmentioning
confidence: 93%
“…Using prescription statistics for several drugs and age groups for several diagnoses, the Disease Analyzer database was found to be a representative database of clinical practices in Germany [ 15 ]. Finally, several studies focusing on female cancers and using the same database have already been published [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%